2013
DOI: 10.1111/acel.12166
|View full text |Cite
|
Sign up to set email alerts
|

H3K4 demethylase activities repress proliferative and postmitotic aging

Abstract: Homeostasis of postmitotic and proliferating cells is maintained by pathways that repress stress. We found that the Caenorhabditis elegans histone 3 lysine 4 (H3K4) demethylases RBR-2 and SPR-5 promoted postmitotic longevity of stress-resistant daf-2 adults, altered pools of methylated H3K4, and promoted silencing of some daf-2 target genes. In addition, RBR-2 and SPR-5 were required for germ cell immortality at a high temperature. Transgenerational proliferative aging was enhanced for spr-5; rbr-2 double muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 49 publications
2
41
1
Order By: Relevance
“…A recent report (Alvares et al, 2013) suggested that spr-5(by134) mutant worms only displayed a transgenerational fertility defect at the elevated temperature of 25°C but not at 20°C. This result was contrary to the initial results reported by (Katz et al, 2009) as well as to our observations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report (Alvares et al, 2013) suggested that spr-5(by134) mutant worms only displayed a transgenerational fertility defect at the elevated temperature of 25°C but not at 20°C. This result was contrary to the initial results reported by (Katz et al, 2009) as well as to our observations.…”
Section: Discussionmentioning
confidence: 99%
“…This result implies that although RSD-2, RSD-6, and SPR-5 repress spermatogenesis gene expression, SPR-5 regulates a distinct repertoire of targets. Thus, the transgenerational sterility phenotype of rsd-2/-6 mutants is distinct from those of alg-3/-4, csr-1, and spr-5 mutants (29).…”
Section: Small Rnas Targeting Spermatogenesis Genes Are Perturbed In Rsdmentioning
confidence: 91%
“…H3K4me3 level has been correlated to gene expression (Ruthenburg et al, 2007) and, accordingly, loss or downregulation of KDM5 members has been associated with aberrant transcription, albeit the effect is often limited to minor gene expression changes (Albert et al, 2013;Alvares et al, 2014;Christensen et al, 2007;Dey et al, 2008;Iwase et al, 2007Iwase et al, , 2016Schmitz et al, 2011;Tahiliani et al, 2007). As the contribution of RBR-2 to transcriptional control at a global level has not been assessed, we analyzed the transcriptome of rbr-2(tm3141) worms by RNA sequencing (RNA-seq).…”
Section: Loss Of Rbr-2 Is Associated With Aberrant Gene Expressionmentioning
confidence: 99%
“…Interestingly, animals mutant for rbr-2 are viable and show mild phenotypes related to lifespan regulation (Alvares et al, 2014;Greer et al, 2010Greer et al, , 2011, germline maintenance (Alvares et al, 2014), axon guidance (Mariani et al, 2016) and vulva formation (Christensen et al, 2007). Therefore, C. elegans offers a unique opportunity to study the functional roles of H3K4me3/2 demethylase in the absence of gene redundancy.…”
Section: Introductionmentioning
confidence: 99%